Dolphins : all the latest facts from the field - Swanson, Jennifer; Jackson-Ricketts, Justine (Absolute expert., 2018)
Presents a collection of facts about dolphins ranging from their typical physical features and behaviors to how to become a dolphin trainer and researcher. Includes diagrams, resources for further information, and color photographs.